2010
DOI: 10.1128/jvi.01366-10
|View full text |Cite
|
Sign up to set email alerts
|

Effective Formation of the Segregation-Competent Complex Determines Successful Partitioning of the Bovine Papillomavirus Genome during Cell Division

Abstract: Effective segregation of the bovine papillomavirus type 1 (BPV1), Epstein-Barr virus (EBV), and Kaposi's sarcoma-associated human herpesvirus type 8 (KSHV) genomes into daughter cells is mediated by a single viral protein that tethers viral genomes to host mitotic chromosomes. The linker proteins that mediate BPV1, EBV, and KSHV segregation are E2, LANA1, and EBNA1, respectively. The N-terminal transactivation domain of BPV1 E2 is responsible for chromatin attachment and subsequent viral genome segregation. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 75 publications
(128 reference statements)
0
16
0
Order By: Relevance
“…Recently, Silla et al [158] have reported that the formation of the BPV-1 E2 segregation complex is Brd4 independent, which is also the case for all HPVs [159]. Silla et al [158] additionally concluded that the formation of segregation-competent complexes depends on a certain protein level threshold and that multiple E2 molecules are present in a single segregation complex together with cellular proteins, including certain components of the transcription machinery.…”
Section: Papillomavirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Silla et al [158] have reported that the formation of the BPV-1 E2 segregation complex is Brd4 independent, which is also the case for all HPVs [159]. Silla et al [158] additionally concluded that the formation of segregation-competent complexes depends on a certain protein level threshold and that multiple E2 molecules are present in a single segregation complex together with cellular proteins, including certain components of the transcription machinery.…”
Section: Papillomavirusesmentioning
confidence: 99%
“…shown that the segregation complex in papillomaviruses contains multiple E2 proteins and also the viral genome should contain at least 5 E2 protein recognition sites [158], it can be expected that a strong chromosomal binding is needed to assure efficient partitioning during cell division. Also, the local organization of chromatin is expected to greatly influence the ability of binding nanoparticles during mitosis.…”
Section: Viral Chromatin Tethering Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histones were immunoprecipitated with antibodies for H3 (ab1791; Abcam), H3Ac (06-599; Millipore), and H3dimeK4 (07-030; Millipore). Brd4 was immunoprecipitated with 2 g each of rabbit polyclonal antibodies Brd4B and Brd4C (47). DNA was extracted from immunoprecipitated and input material and analyzed in triplicate by quantitative PCR (qPCR) on the 7900HT real-time PCR system (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study using chimeric BPV1 E2 proteins has shown that attachment of the protein to chromatin is not sufficient for proper segregation. Successful partitioning of virus genomes during cell division is determined by effective formation of the segregation-competent complex which does not necessarily involve the Brd4 protein (Silla et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 99%